UX.br: um modelo de maturidade de experiência de usuário para aplicações governamentais - Melo, Diogo Nazareno Almeida de (2023)
Electronic government (e-gov) is implemented in many countries as a way to improve and/or increase the efficiency and effectiveness of service delivery in the public sector. Despite advances, many government agencies face challenges when implementing e-government. One of the challenges concerns designing applications that meet the needs of citizen users while there is a low level of adoption of e-government services by citizens. The suggested quality of use, in interactive computer systems, that represents a good interaction between users and the products they use is the User Experience (UX), which concerns a person’s perceptions and reactions that result from the use or anticipated use of a product, system or service. One of the current challenges in the field of UX Design is precisely the institutionalization of UX, specifically at the government level. Just as governments need maturity models for their most effective implementation, they also need a UX eye for their software development projects. Many maturity models related to UX and usability have been proposed in the last decades, however these focus on describing the current maturity of an organization, not helping the organization to advance to the next stage. Another point that deserves attention is that the UX maturity models were designed for organizations in general, without a specific focus on e-government. And finally, these models are not specifically intended for Brazilian governments, in the most diverse areas (health, education, finance, etc). In this sense, this work has the general objective of helping government organizations to increase their UX maturity by proposing a maturity model more focused on Brazilian UX and e-government. For this, we did a bibliographical research and investigated the current state of some Brazilian government agencies in relation to the adoption of UX in their projects. Then we proposed a UX maturity model for government institutions. Finally, we carried out action research in a Brazilian government organization to evaluate the proposed model.